Aplikasi Transshipment Pada Pendistribusian Produk - Titik Chusnia (Jurnal Teknik Industri, 2003)
The company exploit 2 source to firlfill requirement in every marketing location directly from warehouse as according to request. This matter is very require very big delivery expense. So that this research is raised to analyse better distribution column pattern with product delivery expense which minimum. In this analysis model transshipment used for planning of pattem of band of distribution with analysis of previous travelled distance so that a source eam the target personating conversely the target eam the source personating. Analyse this early from forecastingo f requestw ith methodo f linear trend and trend eksponensial. And then selected by plan of marketing for month March - Juny 2004 pursuant to result of smallest MAPE. Herein after the calculation analyse distribution use method of VAM for early solution and method of MODI for solution ofoptium constructively software QS. Total cost which must be released by company before conducted by analysis equal to Rp. 44.722.286a nd after conductedb y analysisw ith method transshipmenty ielding pattern of distribution of proposal and total cost of delivery equal to Rp. 36.2'14.082s, o that can be conducted by thrift equal to Rp. 8.508.204 or by prosentase equal to 19%.